Constraints to production, processing and marketing of sweet-potato in selected communities in Offa Local Government Area, Kwara State Nigeria (2007)
Offa Local Government Area is one of the major sweet-potato growing areas of Nigeria. Sweet potato is grown mainly on smallholder farms and concentrated particularly in communities in Offa Local Government Area. This study randomly selected 90 small scale farmers purposively from 9 communities to investigate constraints to production, processing and marketing of sweet-potato. Data were collected using an interview schedule. Results indicated that yields of 4-7 tonnes per hectare obtained by smallholder farmers are about 20-35 percent of the crop's potential yield. Reasons for this low output are limited cultivated land, lack of improved practices, poor storage facilities, lack of credit facilities, lack of extension training, poor transportation and high cost of input. Also, marketing of the crop is dominated by middlemen, to whom most of the profit accrue, thereby serving as a disincentive to the smallholder farmers. There is, therefore, a need for adoption of improved production techniques, development of appropriate and affordable storage and processing technologies, more efficient distribution and marketing systems and an effective extension service to improve current sweet-potato production in Nigeria.